Improving the Self-Assessment Tools for Training in Speaking to Grade Seven Students of Junior High School - F.Simatupang F.Simatupang; Y.Salamanang Y.Salamanang; A.Tampubolon A.Tampubolon; F.Sianipar F.Sianipar; N.Sinaga N.Sinaga (Jurnal sosial dan sains, 2022)
The main purpose of this study was to improve a self-assessment tool for speaking competency of the seven grade students of junior high school. The focus of this study was specifically on; 1) finding out the types of self-assessment needed to be improved; 2) Improving the prototype of a self-assessment tool; and 3) examining the quality of the improved self-assessment tools. This study used R&D method of Gall & Borg (2003) as design model. The subjects of this study were six English teachers and a syllabus for the seven grade students of junior high school. The data were obtained through questionnaire, interview, observation and syllabus analysis. The results revealed that there were two form of self-assessment tools needed to be developed, namely linguistic aspect and non-linguistic aspect self-assessment. The prototype of self-assessment tools were improved by considering the need analysis results and grand theory. The tools were validated and revised by two expert judges and user judges. Based on the validation from expert judges and user judges, the quality of the improved self-assessment tools was categorized as excellent instruments with very high validity.